Influência do uso de diferentes concentrações de agente reticulante na produção de filmes biodegradáveis à base de soro de leite e gelatina - Antoniazzi, Carolina (My University, 2023)
Synthetic polymeric materials are necessary in the structuring of products due to their mechanical characteristics and low. However, they may be derived from petroleum, a non-renewable source with limited reserves, thus the need arises for the development of biodegradable polymers obtained from biomass. Whey powder, a waste product of the dairy industry, is an alternative in the substitution of raw material of fossil origin by giving the final product flexible characteristics and absence of color and odor. The objective of this work is to evaluate films of different formulations produced based on whey protein and gelatin by casting technique. The results obtained were compared with a synthetic polymer based on PCW used in female external absorbent packaging. For the formulation of the films produced, in addition to whey powder and gelatin as the main and secondary raw materials, respectively, distilled water (solvent), glycerol (additive) and chitosan (additive) were also used in equal amounts and citric acid (crosslinker) in different proportions of 10%, 20%, 30% and 40% on a mass basis. The addition of citric acid resulted in the increase in the thickness of the films in addition to the increase in the solubility of the films with the gradual addition of citric acid. The contact angle test revealed that only the formulations with higher concentration of citric acid are hydrophilic. The elongation of the sample AC20 10 (14.99 %) showed the closest result compared to the standard (40.13 %). The morphological analysis showed that the produced films have uniform and dense structures, regardless of the composition. The FTIR spectra of the films produced revealed similar behaviors, with the presence of characteristic whey bands only in the finger print region, and the addition of citric acid highlighted the increase in the degree of esterification as the crosslinker concentration increased. The films produced showed lower thermal stability compared to the standard (-93.65 % mass loss), and the increase in the concentration of citric acid resulted in a decrease in the mass loss in the films produced, between 74.85 % and 79.81 %. The glass transition temperatures of the films produced (between 19.75 ºC and 22.35 ºC) were close to the standard (23.27 ºC). The characterization revealed that the films produced with 10 % and 20 % (m/m) of citric acid have the potential to be used as packaging for feminine sanitary napkins and the films with 30 % and 40 % (m/m) of citric acid were discarded as an option for this application, mainly due to the high degree of solubility presented, which could generate future problems. The study of the proposed application for films produced based on whey and gelatin is promising, since there is little literature regarding the suggested application. [resumo fornecido pelo autor]
Os materiais poliméricos sintéticos são necessários na estruturação de produtos devido às suas características mecânicas e baixo. No entanto, pode serem derivados do petróleo, fonte não renovável com reservas limitadas, surge assim a necessidade de desenvolvimento de polímeros biodegradáveis obtidos a partir de biomassa. O soro de leite em pó, resíduo da indústria de laticínios, é uma alternativa na substituição de matéria-prima de origem fóssil por conferir ao produto final características flexíveis e ausência de cor e odor. O objetivo deste trabalho é avaliar filmes de diferentes formulações produzidos a base de proteína do soro de leite e gelatina por meio da técnica de casting. Os resultados obtidos foram comparados com um polímero sintético à base de PCW utilizado em embalagens de absorvente externo feminino. Para formulação dos filmes produzidos, além do soro de leite em pó e gelatina como matérias-primas principal e secundária, respectivamente, também foi utilizada água destilada (solvente), glicerol (aditivo) e quitosana (aditivo) em quantidades igual e ácido cítrico (reticulante) em diferentes proporções de 10 %, 20 %, 30 % e 40 % em base mássica. A adição de ácido cítrico resultou no aumento na espessura dos filmes, além do aumento da solubilidade dos filmes com a adição gradual de ácido cítrico. O teste de ângulo de contato revelou que apenas as formulações com maior concentração de ácido cítrico são hidrofílicas. O alongamento da amostra AC20 10 (14,99 %) apresentou resultado mais próximo em relação ao padrão (40,13 %). A análise morfológica mostrou que os filmes produzidos possuem estruturas uniformes e densas, independentemente da composição. Os espectros FTIR dos filmes produzidos revelaram comportamentos semelhantes entre si, com a presença de bandas características do soro de leite apenas na região de finger print, sendo que a adição de ácido cítrico ressaltou o aumento do grau de esterificação conforme houve o aumento da concentração de reticulante. Os filmes produzidos apresentaram menor estabilidade térmica em relação ao padrão (-93,65 % de perda de massa), sendo que o aumento da concentração de ácido cítrico resultou na diminuição da perda de massa nos filmes produzidos, entre 74,85 % e 79,81 %. As temperaturas de transição vítrea dos filmes produzidos (entre 19,75 ºC a 22,35 ºC) foram próximas ao padrão (23,27 ºC). A caracterização revelou que os filmes produzidos com 10 % e 20 % (m/m) de ácido cítrico têm potencial para serem utilizados como embalagens de absorventes femininos e os filmes com 30 % e 40 % (m/m) de ácido cítrico foram descartados como opção para essa aplicação, principalmente pelo alto grau de solubilidade apresentado, podendo gerar problemas futuros. O estudo da aplicação proposta para filmes produzidos à base de soro de leite e gelatina são promissores, visto que há pouca literatura referente à aplicação sugerida. [resumo fornecido pelo autor]
Keywords: Engenharia química; Biopolímeros; Biodegradação; Filmes finos